2015
DOI: 10.7575/aiac.ijalel.v.4n.6p.23
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intermediate EFL Learners' Communication Apprehension, Willingness to Communicate, and Speaking Ability

Abstract: Speaking is the first to be acquired in the process of language production. In parallel, the absence of communication apprehension and the presence of willingness to communicate are the essential prerequisites for stringing words together. The purpose of the current study, therefore, was to investigate the underlying patterns of the relationship between communication apprehension (CA), willingness to communicate (WTC), and speaking ability with regard to different contexts and receivers. In so doing, to assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results demonstrate that the e-module is effective in improving students' speaking abilities, while also enhancing their understanding of cultural values. This finding aligns with evidence from Puentedura's (2006) SAMR Model, which emphasizes that technology can redefine learning tasks, leading to the creation of new tasks, previously inconceivable. As such, the introduction of this e-module, which combines linguistic and cultural education, can be seen as a valuable step forward in language education.…”
Section: Discussionsupporting
confidence: 86%
“…The results demonstrate that the e-module is effective in improving students' speaking abilities, while also enhancing their understanding of cultural values. This finding aligns with evidence from Puentedura's (2006) SAMR Model, which emphasizes that technology can redefine learning tasks, leading to the creation of new tasks, previously inconceivable. As such, the introduction of this e-module, which combines linguistic and cultural education, can be seen as a valuable step forward in language education.…”
Section: Discussionsupporting
confidence: 86%
“…They also concluded that a majority of learners experience a low level of WTC when it comes to learning L2, which prevents L2 learning development. In a similar vein, the results of a study by Rahmatollahi and Famil Khalili (2015) revealed that WTC and speaking ability are positively correlated. MacIntyre et al also (2002) hold that many EFL learners do not enjoy the required level of WTC needed for communication.…”
Section: Introductionmentioning
confidence: 75%
“…Sincelanguagelearningnecessarilyinvolvesoralparticipation,itisreasonabletoexpectthat somestudentswillexperienceCAinsuchcourses.Specifically,CAplaysacriticalroleinstudents' second language acquisition (Rahmatollahi & Khalili, 2015). Literature suggests that language instructorsmustaddressstudents'CAinordertofacilitatesecondlanguageacquisition (McCroskey, Fayer&Richmond,1985).StudentswhoexperienceCAintheirnativelanguagealsoexperience CAintheirsecondlanguage (Jung&McCroskey,2004),andstudents'levelofCAintheirfirst languageestablishesabaselinefortheirlevelofCAinasecondlanguage (McCroskey,Gudykunst, &Nishida,1985).CAlevelstendtobehigherinone'ssecondlanguagethaninone'snativetongue (Richmond,McCroskey,McCroskey,&Fayer,2008),althoughsomeevidencetothecontraryexists in particular circumstances (Rimkeeratikul, 2015).…”
Section: Literature Review Communication Apprehension and Language Le...mentioning
confidence: 99%